Raised serum chondroitin sulfate epitope level in ovarian epithelial cancer - Pothacharoen P. (2014)
Objective: To determine the value of serum chondroitin sulfate epitope WF6 and hyaluronan (HA) levels as a biomarker for early detection of ovarian epithelial cancer and other gynecological disorders. Method: Serum WF6 CS epitope and HA were measured in 91 patients with ovarian epithelial cancer, 39 patients with non-cancer gynecological disorders and 30 healthy women. Serum chondroitin sulfate (CS) WF6 epitope was determined by a competitive immunoassay with the monoclonal antibodies WF6, which specifically recognizes an epitope in native CS chains. In addition, serum HA concentration was measured by an ELISA-based assay with a biotinylated affinity HA-binding proteins. Results: The serum concentration of CS (WF6) epitope was highly increased in epithelial types of ovarian cancer and at all stages of development (p < 0.005). Serum HA in ovarian cancer patients was significantly higher than normal controls (p < 0.05). Conclusion: These results reflect changes in ECM metabolism in progressive ovarian cancer, which cause an increase in serum CS epitopes and HA. Therefore, serum CS epitopes may provide useful biomarkers for cancers and other disorders of the ovary. Measurement of serum HA provided complementary information, which may be useful as a discriminator between benign ovarian disorders and malignant ovarian diseases. © 2006 The Japanese Biochemical Society.